Committee for Employment and Learning Report on its Consideration of the Legislative Consent Memorandum Concerning the Enterprise Bill (Apprenticeships - Data Sharing Provisions). ([2016]) - Northern Ireland., Assembly., Committee for Employment; Learning,
No abstract available